Man and bird in the Palaeolithic of Western Europe - Eastham, Anne, (Archaeopress Archaeology, 2021)
This text considers the nature of the interaction between birds and hunter-gatherers in Western Europe. It examines aspects of avian behaviour and the qualities targeted at different periods by hunter-gatherers, who recognised the utility of the diversity of avian groups in various applications of daily life and thought.